Editorial - Thapa, Abhijeet (Nepalese Culture, 2026)
The current volume 19 of Nepalese Culture: A Peer Reviewed Journal features 12 selected articles that have successfully passed the double-blind peer review process in accordance to the journal's requirements. Throughout the process, there have been serious and dedicated efforts to beget this volume in contributing standards. Needless to say, but I cannot and should not proceed without acknowledging all those who contributed for this in one way or the other. At the cusp of the publication, I extend my sincere thanks, on behalf of the editorial board, to all the dedicated contributors and congratulate them on the selection and publication of their articles in this journal. The time they have invested, their venture into the topics, repeated revisions and resubmissions all point to the authors’ subtle dedication and sincere urge for task accomplishments. Similarly, I have my deep gratitude to our editors who took dedication to the next level, reviewers who meticulously worked but remain anonymous, advisory board who offered “leans” on patronage and the TU print house for consistent support. I extend my sincere thanks to the HoD for his consistent trust upon our team and also to the colleagues of the Central Department of Nepalese History, Culture and Archaeology at Tribhuvan university for their well- wishes! It would be appropriate to begin with depictions on the types of research we have here prior to presenting their concise summary. Research articles have covered a wide range of themes of spiritual well-being, didactic and persuasive narratives on Vedic rituals, mantra, tangible and intangible cultural riches, failure on tourism governance to interesting indigenous and ethnographic studies. The perspectives, findings and discussions on noble and emergent or new issues raised by our valued authors have spanned in diverse themes and purpose-oriented approaches. These all, hopefully, set up avenues for the readers to think, rethink and surmise the cultural riches of Nepal. The researchers have either addressed or directly studied components of World Heritage sites, employed comparative paradigms to compare Nepal and other countries, engaged with Hindu epistemological traditions, and contributed to the study of tangible and intangible cultural heritage.